The Effect of Macroeconomic and Bank-Specific Variables to Risk-Taking of Islamic Bank in Indonesia - Fakhrunnas, Faaza (International Journal of Islamic Economics and Finance (IJIEF), 2019)
This study aims to delineate the relationship between macroeconomic factors and bank-specific variables to risk-taking of Islamic bank. Adopting panel co-integration approach, this study posits macroeconomic and bank-specific factors as exogenous variables consisting to interest rate, exchange rate, inflation, bank size and equity to asset ratio. Risk-taking as endogenous variable has proxies non-performing loan or financing and bankruptcy risk. By using quarterly data from 2010-Q4 to 2017-Q4, this study finds the risk-taking behavior of all banks has long-term relationship with macroeconomic factors. In terms of bank specified characteristic, bank size becomes substantial factor for the bank’s risk mitigation. When the samples are grouped based on Islamic bank’s size, the big size of Islamic bank has no long-term co-integration to macroeconomic variables. As opposed to that, the middle and small size of Islamic bank have long-term relationship to macroeconomics factors and all macroeconomic variables affect the risk-taking of Islamic bank. It concludes that the medium and small size of Islamic banks are more vulnerable from external shock.